Nanocosmetics and Nanomedicines New Approaches for Skin Care - Beck, Ruy.; Guterres, Silvia; Pohlmann, Adriana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book contains a summary of the most important nanocarriers for skin delivery. Although (3z(Bnanocosmetics(3y (Bis a subject widely commented in the academy and the beauty industry, a book covering the skin care treatments using nanotechnological approaches with cosmetics and nanomedicines is still missing, therefore the need for this publication. This book is divided in three parts: The first one (Part A) is devoted to a brief review on the main topics related to the skin delivery and to the introduction of the subject (3z(Bnanocosmetics(3y(B. The second part (Part B) presents different types of nanocarriers applied as skin delivery systems for cosmetics or drugs. The last part (Part C) shows a wide range of applications of nanotechnology on the skin care area as well as on dermatocosmetic and dermatological fields.s
Part A: Fundamentals of Skin Delivery -- Part B: Nanocarriers for Skin Care and Dermatological Treatments -- Part C: Applications of Nanocosmetics and Nanomedicines for Skin Treatments.
Keywords: Pharmaceutical technology; Pharmacy; Dermatology; Engineering; Biomaterials; Nanotechnology; Materials Science; Nanotechnology; Pharmacy; Dermatology; Biomaterials; Nanotechnology and Microengineering; Pharmaceutical Sciences/Technology.